"Coal is Not Just a Job, It's a Way of Life": The Cultural Politics of Coal Production in Central Appalachia. (19th October 2017) - Lewin, Philip G
Abstract: Since beginning operations in Central Appalachia, coal producers have economically exploited residents and exposed them to severe health risks associated with pollution. Despite causing these problems, the industry enjoys vigorous popular support. Drawing on nine months of immersive ethnography in "Shale County, " this article examines why many Appalachians endorse the coal industry despite its negative externalities. I find that Appalachia's subordinate relationship to the rest of the nation plays a profound role in conditioning the region's pro-industry, anti-environmental views. Many Appalachians feel like the federal government neglects them, and like urban America, devalues them. Drawing upon Antonio Gramsci's theory of hegemony, I show how the coal industry capitalizes upon these feelings by promoting coal heritage —a carefully curated cultural construction that emphasizes selective aspects of Appalachian history while erasing those that challenge its domination. Coal heritage, I show, conveys environmentalism as an attack on Appalachians' right to economic opportunity, their role in the national division of labor, and their moral worth. It frames industry representatives, on the other hand, as guardians of regional interests and values.